Abnormal Default Mode Network Homogeneity in Treatment-Naive Patients With First-Episode Depression - Gao, Yujun; Wang, Menglin; Yu, RenQiang; Li, Yaping; Yang, Ying; Cui, Xiangxiang; Zheng, Jinou (Frontiers in Psychiatry, 2018)
Background and Objective: Default-mode network (DMN) is important to solve a broad-scale cognitive problem which occurs in patients who suffer with first-episode treatment-naive depression. However, there is not very much information related to how much network homogeneity (NH) of DMN changes in patients who suffer with first-episode treatment-naive depression. In this paper, taking patients suffering with first-episode treatment-naive depression at rest as examples, NH is utilized to explore NH of DMN. Methods: Participants comprise 66 patients and 74 contrasts who are controlled in age, gender, education and health and have experienced resting-state functional magnetic resonance imaging (rs-fMRI) and attentional network test (ANT). To assess data, the study utilizes NH and independent component analysis (ICA), and Spearman’s rank correlation analysis is performed among significantly abnormal NH in depression patients and clinical measurements and ANT scores. Results: Under the comparison with the control group, there are some trends for those patients who suffer with first-episode treatment-naive depression: the decline of NH in bilateral angular gyrus (AG) as well as the growth of NH in the bilateral Precuneus (PCu) and posterior cingulate cortex (PCC). Meanwhile, it has been found that those suffering with first-episode treatment-naive depression are longer in executive control reaction time (ECRT). Consequently, there is no obvious relation of abnormal NH values with clinical variables. Conclusions: These consequences suggest that, among patients who suffering with first-episode treatment-naive depression, there are abnormal NH values of DMN and an emphasis on how significant DMN is for the pathophysiology related to cognitive problems. On the other hand, the study also finds that abnormality exists in executive function for patients who suffer first-episode treatment-naive depression.